030 Taking CHARGE of the situation: a walk out brief to prepare staff for non-clinical emergencies on transfer. (December 2018) - Roberts, C
Abstract : Introduction: The Children's Acute Transport Service (CATS) is a stand-alone paediatric critical care transport service that performs approximately 1200 transfers each year in the North Thames region. Transfers are primarily by road in a dedicated ambulance, with approximately 25 flights per year (fixed wing and rotary). We perform international transfers and repatriations. All CATS rotational staff undertake annual updates to ensure continuing professional and educational objectives are achieved. Training previously focused on clinical situations and emergencies, with limited time allocated for non- clinical incidents including tyre blow out or ambulance evacuation. To address this, annual update days were redesigned to accommodate these situations. Methods: Continuing our collaboration Survival Wisdom (a company owned by ex-military personnel) we redesigned the study day to include, psychological response to danger, threat analysis in differing scenarios (inner city, motorway, rural), knowledge of CATS major incident plan, aeromedical, trapped in a lift, and ambulance evacuation. The format was a mix of lectures, table top exercises, and scenarios. Training was multidisciplinary and attended by all members of the transfer team. Scenarios have been developed from reported critical incidents. Results: A total of 85 people have attended the course since 2015, including doctors, advanced nurse practitioners, nurses, ambulance technicians and administrators. One day from each year was chosen to compare evaluation scores. All evaluations are anonymous. All categories scored good to excellent, with sim scenarios consistently scoring the highest. Comments from attendees reflect this: 'Scenarios challenging and thought-provoking…. good to build on scenarios from last year, good to do sim in unusual circumstances' Evacuation times were compared from year 1 to year 3 reducing from 3 min to 30 s or less. Discussion and Conclusion: The course has been running for three years. Staff are more familiar with the major incident plan The course has been evaluated well and continues to be developed following feedback and staff demonstrate quicker decision making and are able to evacuate ambulance in 30 s or less compared to an average of 3 mins in the first year.